PERCEPTION OF BATARAZA I DISTRICT’ TEACHERS ON MODULAR DISTANCE LEARNING (MDL) - Michael D. Yayen; Jergen Jel C. Labaria (Scholar Express Journal, 2021)
Corona Virus Disease (COVID-19) caused many problems not just in our country but rather the whole world. Every sectors and departments are affected and one of these is the Department of Education (DepEd). With this reason, the traditional face-to-face classes is being prohibited and modular distance learning is been allowed by our president. This study conducted to determine the level of perception of the selected elementary teachers of Bataraza I District on modular distance learning. And determine the identified advantages and disadvantages of modular distance learning in this time of pandemic. The study utilized descriptive design using survey method which was administered through Google forms and sent through the email or messenger of the respondents together with the informed consent. Stratified sampling was utilized to identify the teachers according to their demographic profile. Frequency, percentage and mean was used to analyze and interpret the data obtained from the respondents. Significant findings of the study revealed that the level of perception, confidence, satisfaction, and experiences of selected elementary teachers is said to be on neutral or average with a composite mean of 2.70. Likewise, the study recommends that there should be a little changes in the modules to be more effective to both teachers and pupils.
Keywords: Corona Virus Disease; Modular Distance Learning; Distance Learning Approach; Self-Learning Module